Modeling and Performance Evaluation of Solar Cells Using I-V Curve Analysis - Hasan A.A.Q.; Alkahtani A.A.; Amin N. (Springer Science and Business Media Deutschland GmbH, 2024)
The global photovoltaic (PV) capacity has expanded considerably, especially in buildingsand power plants that are stand-alone orgrid-connected PV systems. Further research into fault detection is required to identify various faults on different PV levels to keep the PV systems working at optimal efficiency.We provide a Simulink model of a single solar cell for estimating the currentvoltage (I-V) properties of a real solar cell. The advantages and limitations of using the I-V curve as a diagnostic tool for PV system faults are discussed. In addition, the impact of series and shunt resistances on solar cell performance is highlighted and linked to related defects and degradation. Results of the proposed solar cell model confirmed its ability to mimic the real solar cell I-V curve with a very small percentage of error, around 1%. Furthermore, FF revealed the highest percentage of error of 1.2% due to the additional wire losses in real solar cell. Thus, the proposed solar cell model could be implemented to investigate degradations that have complex I-V curve behavior and improve the PV faults monitoring systems. 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.